2009
DOI: 10.1371/journal.pone.0008256
|View full text |Cite
|
Sign up to set email alerts
|

Neural Population-Level Memory Traces in the Mouse Hippocampus

Abstract: One of the fundamental goals in neurosciences is to elucidate the formation and retrieval of brain's associative memory traces in real-time. Here, we describe real-time neural ensemble transient dynamics in the mouse hippocampal CA1 region and demonstrate their relationships with behavioral performances during both learning and recall. We employed the classic trace fear conditioning paradigm involving a neutral tone followed by a mild foot-shock 20 seconds later. Our large-scale recording and decoding methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
96
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(108 citation statements)
references
References 65 publications
12
96
0
Order By: Relevance
“…Because duration is encoded during trace fear conditioning without animals engaged in prospective timing, it is of interest to characterize the hippocampal network during this process. With traces as long as 20 s, hippocampal neurons activate at the expected time of the shock when it is omitted ( [105]; see also [106]). Different neurons also activate during the trace, as has been reported in other trace conditioning paradigms, but the response profiles of these cells are more heterogeneous across the population.…”
Section: Retrospective Duration Memory In the Hippocampusmentioning
confidence: 99%
“…Because duration is encoded during trace fear conditioning without animals engaged in prospective timing, it is of interest to characterize the hippocampal network during this process. With traces as long as 20 s, hippocampal neurons activate at the expected time of the shock when it is omitted ( [105]; see also [106]). Different neurons also activate during the trace, as has been reported in other trace conditioning paradigms, but the response profiles of these cells are more heterogeneous across the population.…”
Section: Retrospective Duration Memory In the Hippocampusmentioning
confidence: 99%
“…In behaving animals, in vivo neuronal ensemble recordings showed that CA1 neurons not only contribute to form place fields (45,46), but also exhibit specific encoding patterns to contextual stimuli (47). Moreover, the spatial or contextual information seems to interact with each other in a population of CA1 neurons (48).…”
Section: Discussionmentioning
confidence: 99%
“…In our hands, a single-unit can be followed over several recording sessions (30 min each) that span a period of 3 days, reflecting an intersession stability As microdrive components become more lightweight and the software to analyze neural signals improves, the library of potential brain targets and testable hypotheses within neuroscience continues to expand. It is clear that, since their inception 1,12 , brain recordings from awake behaving animals have greatly advanced our understanding of how neurons and networks of neurons encode behaviorally relevant events 3,4,13,14 . In particular, brain recordings from genetically modified mice have allowed the identification of molecular cascades that are crucially involved in neural encoding [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…The ability to record electrical activity from many brain regions in freely behaving animals is, however, a more recent technology that is becoming increasingly common as the software packages for the acquisition, analysis and discrimination of neural signals becomes more sophisticated and user-friendly 3,4 . The technological advances on the software side have also been accompanied by reductions in the weight and bulk of the implantable devices, which have been scaled down sufficiently for recording in small mammals, such as mice.…”
Section: Introductionmentioning
confidence: 99%